DNA Methylation in Healthy Older Adults With a History of Childhood Adversity—Findings From the Women 40+ Healthy Aging Study - Fiacco, Serena; Gardini, Elena Silvia; Mernone, Laura; Schick, Lea; Ehlert, Ulrike (Frontiers in Psychiatry, 2019)
Background: Adversity in early development seems to increase the risk of stress-related somatic disorders later in life. Physiologically, functioning of the hypothalamic-pituitary-adrenal and hypothalamic-pituitary-gonadal axes is often discussed as long-term mediators of risk. In particular, DNA methylation in the glucocorticoid receptor gene promoter (NR3C1) has been associated with type and strength of early life adversity and subsequent effects on HPA axis signaling in humans. Animal studies, moreover, suggest changes in DNA methylation in the estrogen receptor gene (ERα) upon early life adversity. We investigated the association of type and severity of childhood adversity with methylation in NR3C1 and ERα, and additionally considered associations between methylation and steroid hormone secretion. Methods: The percentage of methylation within the NR3C1 promoter and the ERα CpG island shore was investigated using dried blood spot samples of 103 healthy women aged 40-73 years. Childhood adversity was examined with the Childhood Trauma Questionnaire. Linear regression analyses were performed with methylation as dependent variable and the experience of emotional abuse and neglect, physical abuse and neglect, and sexual abuse (compared to non-experience) as independent variables. All analyses were controlled for age, BMI, and annual household income. Results: Overall, over 70% of the sample reported having experienced any kind of abuse or neglect of at least low intensity. There were no significant associations between childhood adversity and methylation in NR3C1 (all p >.10). Participants reporting emotional neglect or abuse showed significantly higher methylation in the ERα gene than those who did not (p< .05). Moreover, participants reporting sexual abuse or physical abuse showed higher methylation in ERα than those who did not, with borderline significance (p < .10). Higher levels of adversity were associated with higher levels of ERα gene methylation. Conclusion: In resilient women, early life adversity does not seem to result in NR3C1 hypermethylation in midlife and older age. This is the first study in humans to suggest that childhood adversity might, however, epigenetically modify the ERα CpG island shore. Further studies are needed to gain a better understanding of why some individuals remain healthy and others develop psychopathologies in the face of childhood adversity.